Systems biology of apoptosis signaling networks - Lavrik, Inna N. (Current opinion in biotechnology, 2010)
Apoptosis is a complex but highly defined cellular program of cell demolition. Apoptosis can be triggered by the extrinsic or the intrinsic death pathways. Deregulation of apoptosis leads to a number of serious diseases, including cancer. A substantial progress in understanding apoptotic signaling networks has been recently achieved using systems biology. This review will give an overview of the contemporary models of apoptotic signaling networks. The potential of the dynamic models, which include all known components of the network, versus the importance of searching for new components of the networks using different screening techniques will be discussed. The further development of apoptotic signaling networks should provide ways to sensitize cells toward apoptosis and provide new therapies for cancer treatment.